IMPACT OF SNORKELING AND DIVING TO CORAL REEF ECOSYSTEM - . Muhidin; Fredinan Yulianda; Neviaty Putri Zamani (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Panggang Island is one of the snorkeling and diving area in the Seribu Islands. Number of tourists increase every year in line with the improving of tourism infrastructure such as tourist boat and dive shops. Tourism activities not only provide economic benefits but also give negative impact on coral reef ecosystem. The results of direct observations showed that there was destructive impact from snorkeling and diving. The most destructive behavior done by snorkeling and diver who has license was stepping on the coral reef. While the most destructive behavior by diver who has no license was holding the coral reef. The continued effect of tourist destructive behaviour grouped into three categories such as rubble, scratches on top of coral colony, and crushed coral colony. Based on the tourism impact analysis showed that diverwho has not been licensed gived the greatest damage impact,it was 13.55% per year of the ecological potential. While the impact of snorkeling touristwas 5.05% and diver who has license gived the smallest effect, it was 2.36%.  Comparison of coral reef data between 2010 and 2016 showed no significant changes to the coral reef, it means that until now coral reefs of Panggang Island still tolerate any disturbances including impact of tourism activities.Keywords : coral reef, diving, snorkeling, tourism, Panggang                      IslandPanggang Island is one of the snorkeling and diving area in the Seribu Islands. Number of tourists increase every year in line with the improving of tourism infrastructure such as tourist boat and dive shops. Tourism activities not only provide economic benefits but also give negative impact on coral reef ecosystem. The results of direct observations showed that there was destructive impact from snorkeling and diving. The most destructive behavior done by snorkeling and diver who has license was stepping on the coral reef. While the most destructive behavior by diver who has no license was holding the coral reef. The continued effect of tourist destructive behaviour grouped into three categories such as rubble, scratches on top of coral colony, and crushed coral colony. Based on the tourism impact analysis showed that diverwho has not been licensed gived the greatest damage impact,it was 13.55% per year of the ecological potential. While the impact of snorkeling touristwas 5.05% and diver who has license gived the smallest effect, it was 2.36%.  Comparison of coral reef data between 2010 and 2016 showed no significant changes to the coral reef, it means that until now coral reefs of Panggang Island still tolerate any disturbances including impact of tourism activities. Keywords : coral reef, diving, snorkeling, tourism, Panggang Island